The Implementation of Balanced Scorecard Perspective Performance Analysis: Case Study of Krispiku MSMEs - Annisa Muthmainnah Ichwan; Irma Syafitri; Mufida Rahmayani; Sri Devi; Yomi Satifa Putri (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
Micro, Small and Medium Enterprises (MSMEs) are one of the important pillars in national economic growth because they have a major contribution to Indonesia's Gross Domestic Product (GDP). In Central Java, the manufacturing sector dominates the structure of the Gross Regional Domestic Product (GRDP). The growth in the number of MSMEs has implications for increasingly fierce business competition. MSME actors are required to be more productive and innovative, therefore a performance appraisal is needed as an evaluation in order to carry out continuous improvement. One method of measuring performance that is considered effective because it is able to measure the company's performance from various aspects, both financial and non-financial, is the Balanced Scorecard. The object of this research is Krispiku MSMEs located in Cilacap, Central Java. This study uses quantitative methods. This study aims to analyze the performance assessment using the Balanced Scorecard on Krispiku SMEs located in Cilacap Regency, Central Java. The results showed that weighting the four perspectives using paired comparison obtained perspective financial as main priority in strategy development company with a value of 0.48. Meanwhile, based on the balanced scorecard analysis, the results show that the productivity of Krispiku's MSMEs is still low and needs to be improved so that Krispiku can get maximum profit.